ANALISIS KETERISIAN CLINICAL DOCUMENTATION PASIEN IGD DAN RAWAT JALAN PADA ELECTRONIC HEALTH RECORD (EHR) DI RUMAH SAKIT AKADEMIK UNIVERSITAS GADJAH MADA - , ERLANGGA GUSMA K, Nuryati, S.Far., MPH. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Indonesian law No. 29 of 2004 that \"any doctor or dentist in medical practice shall make medical records\". Hospital as one of the agency that runs the medical practice then it must hold medical records. The main purpose of organizing medical records were produced quality health information, so it can be used as a basis for making an appropriate policy. To obtain high-quality data, complete, and valid, one way to fill the entire form which has made the hospital, so that the required data can be obtained hospital is complete and thorough. Objective:Knowing the percentage of occupancy and contributes to the lack of clinical documentation form filled emergency patients and outpatients in the Electronic Health Record in the Gadjah Mada Academic Hospital. Method: Type of research is a descriptive study with a qualitative approach to data collection using the study documentation, interviews, and observations. This research design used phenomenological. Research subjects in this study were medical records personnel, emergency physicians, and outpatient physician. Objects in this study were 97 patients emergency clinical documentation and 99 outpatient clinical documentation Electronic Health Record (EHR). For the validation data used source triangulation and techniques triangulation. Subjects used purposive sampling, while the object of study used a random sample calculations. This research was performed at the medical record, emergency and outpatient installation. Results: Occupancy analysis performed on 97 clinical documentation documents emergency patients and 99 outpatients documents at Gadjah Mada University Academic Hospital randomly selected and evenly patient visits by months (January to December) in 2013. The average percentage of occupancy of clinical documentation emergency patients only reached 83.33% and outpatients 80.47%. So it can be said that service medical records have not been able to reach the minimum service hospital that is 100% complete so that the completeness of the medical record must be improved. While the cause of emergency department patients ketidakterisian form and outpatient EHR is 1. Lack of concern for the listing of the physician medical record, 2. Frequent occurrence of communication errors between health professionals, 3. Yet clear SOP.